Thin structure of steel St52, 3N and possible reasons of defect of large-capacity billets AT "YURMASH"; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 4 : Power engineering - Danilov V. I. Владимир Иванович; Valuev D. V. Denis Viktorovich; Ivanov Yu. F. Yuriy Fedorovich; Apasov A. M. Aleksandr Mikhailovich (Power engineering, 2007)
Заглавие с титульного листа